Das metaphysische „sein“ bei Aristoteles: Kopula oder Existenzverb? - Gutberlet, Albert (Alpha omega, 2020)
This article aims at further understanding the meaning and function of the verb “to be” in Aristotle’s Metaphysics: does it express mainly or even exclusively existence or is it used as a copula, linking a subject and predicate? Since the birth of Greek literature, the copula-use has been by far the more common, and so it is also with Aristotle. He even provides us with the nucleus of a theory of the copula, which is not the case with existence in the strict philosophical sense. Analyzing Met. V, 7, VI, 4 and VIII, 2, I conclude that wherever Aristotle tries to determine, what, for being as being, it means “to be”, he refers not to existence, but to some concrete being-such, where the verb “being” functions as a copula. So while metaphysical being does also consistently carry an existential force, regarding its syntactic function it is nonetheless copulative through and through.